Jakarta Sebagai "Service City" dan Pengaruhnya Terhadap Perencanaan Tata Ruang: Pendekatan Sosial Ekonomi - . Hidayat (Journal of Regional and City Planning, 1996)
The Governor of Jakarta has declared that Jakarta will be build and developed to become a "service city". This program is in accordance with the plan of the GOI to develop Indonesia to become a "New Industrializing Country" by the year 2020. There are 5 (five) pillars to support Jakarta as service city: the center of public service, the center of trade and goods distribution, the center of finance, the center of tourism, and the center of society development. One important aspect that should be taken into consideration is spatial planning. There should be a review whether the existing RUTR and RBWK are still in accordance with the program. There also should be a review for factors relating to the building permit (IMB) since the existing IMB has not supported the program of service city.